Food supplements market in Poland and the European Union – regulations and consumption of food supplements in the pre-COVID and COVID era - Strocka, Justyna; Religioni, Urszula; Pinkas, Jarosław (Family Medicine & Primary Care Review, 2025)
The food supplements market has been improving year to year. In 2022, the value of the global food supplements market was USD 164 bn. Forecasts show that this segment is still going to grow. The value of the Polish food supplements market is growing constantly as well, and in 2022, it reached PLN 7.7 bn, which means that the value doubled in comparison to 2015. The COVID-19 pandemic definitely had a serious impact on the observed trend. This also made people care more about their health, as well as to take some prophylactic measures. Despite the wide use of food supplements not only by Poles but also by people all over the world, there are relatively few scientific publications in this area. Due to this, the aim of this article is to collect the knowledge on regulations of the food supplements market as well as the distribution of those products on Polish and European Union markets. The COVID-19 pandemic played a significant role in shaping this trend, and it heightened awareness about health and encouraged people to take preventive measures. In this article, special attention was paid to the influence of the COVID-19 pandemic on changes within the food supplements market.